2007
DOI: 10.1007/s00253-006-0623-z
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the lycopene synthetic pathway in E. coli by comparison of the carotenoid genes of Pantoea agglomerans and Pantoea ananatis

Abstract: The lycopene synthetic pathway was engineered in Escherichia coli using the carotenoid genes (crtE, crtB, and crtI) of Pantoea agglomerans and Pantoea ananatis. E. coli harboring the P. agglomerans crt genes produced 27 mg/l of lycopene in 2YT medium without isopropyl-beta-D: -thiogalactopyranoside (IPTG) induction, which was twofold higher than that produced by E. coli harboring the P. ananatis crt genes (12 mg/l lycopene) with 0.1 mM IPTG induction. The crt genes of P. agglomerans proved better for lycopene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
62
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 29 publications
1
62
1
1
Order By: Relevance
“…Interestingly, even though RCB and RSB come from the same genus (Rhodobacter) and are separated by a short phylogenetic distance (Fig. 3A), they showed a different heterologous complementation pattern in E. coli, as seen in a different pattern of carotenogenic enzymes from P. agglomerans and P. ananatis (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, even though RCB and RSB come from the same genus (Rhodobacter) and are separated by a short phylogenetic distance (Fig. 3A), they showed a different heterologous complementation pattern in E. coli, as seen in a different pattern of carotenogenic enzymes from P. agglomerans and P. ananatis (24).…”
Section: Resultsmentioning
confidence: 99%
“…4D). CrtE has been considered one of the rate-limiting enzymes in carotenoid biosynthesis (24). Therefore, the enhancement of carotenoid production can be explained by CrtEs with different affinities for farnesyl pyrophosphate (FPP) having flexibility in the heterologous carotenogenic machinery assembly.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, nonpathogenic P. ananatis and closely related species have attracted interest in the fermentation industry because they are promising tools in metabolic engineering (23)(24)(25). Recent studies have indicated the potential of P. ananatis for the overproduction of a variety of useful chemicals, including amino acids and related compounds (L-glutamate [26], L-aspartate [27], and L-3,4-dihydroxyphenylalanine [28]), vitamins (pyrroloquinoline quinone [25], ascorbic acid intermediates [29], and vitamin E [30]), and other chemical compounds (2,3-butanediol [X. W. Jiang, 9 May 2007, Chinese Patent Office]). One of the greatest successes is in the development of the L-glutamate fermentation technology, where the characteristic growth of this microbe under acidic conditions (pH approximately 4) has facilitated the fermentative production of glutamate at an acidic pH, which is an environment where glutamate has low solubility, and thus, glutamate production is accompanied by its crystallization in culture (26,31).…”
mentioning
confidence: 99%
“…In recent years, nonpathogenic P. ananatis and its closely related species have attracted the interest of the fermentation industry because they have promise as tools for metabolic engineering (19,21,22). Recent studies have indicated the potential of P. ananatis for overproducing a wide variety of useful materials, including amino acids and related compounds (L-glutamate [23], L-aspartate [24], and L-3,4-dihydroxyphenylalanine [25]), vitamins (pyrroloquinoline quinone [22], ascorbic acid intermediates [54], and vitamin E [26]), and other chemical compounds (2,3-butanediol [X. W. Jiang, 9 May 2007, Chinese Patent Office]). Our present study provides important insights into using the bacterium for the fermentative production of cysteine and related biomaterials.…”
mentioning
confidence: 99%